2021
DOI: 10.1136/bmjsem-2021-001071
|View full text |Cite
|
Sign up to set email alerts
|

Effects of beta-blockers on archery performance, body sway and aiming behaviour

Abstract: ObjectivesThis study aimed to determine the effect of selective (bisoprolol-5 mg) and non-selective (propranolol-40 mg) beta-blockers on archery performance, body sway and aiming behaviour.MethodsFifteen male archers participated in a randomised, double-blind, placebo-controlled, cross-over study and competed four times (control, placebo, selective (bisoprolol) and non-selective (propranolol) beta-blocker trials). Mechanical data related to the changes in the centre of pressure during body sway and aim point f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
0
5
0
1
Order By: Relevance
“…For example, apart from stress, high heart rate may decrease precision in shooting. Nevertheless, research showed that scores were not affected by lowering heart rate through the administration of beta-adrenergic receptor blockers to inhibit the binding process of noradrenaline (Ergen et al, 2021). Moreover, we observed that heart rate changed in response to stress-related factors such as countdown time and shooting order, which supports the idea of heart rate as a stress biomarker associated with performance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, apart from stress, high heart rate may decrease precision in shooting. Nevertheless, research showed that scores were not affected by lowering heart rate through the administration of beta-adrenergic receptor blockers to inhibit the binding process of noradrenaline (Ergen et al, 2021). Moreover, we observed that heart rate changed in response to stress-related factors such as countdown time and shooting order, which supports the idea of heart rate as a stress biomarker associated with performance.…”
Section: Discussionmentioning
confidence: 99%
“…For example, using beta‐blockers metoprolol and oxprenolol before competitions significantly improves shooting performance in skilled shooters, 5,6 which is also a critical reference for the World Anti‐Doping Agency (WADA) to ban beta‐blockers in certain sports. However, the influence of beta‐blockers on performance is still limited and inconclusive in specific sports, such as archery 7 …”
Section: Introductionmentioning
confidence: 99%
“…However, the influence of beta-blockers on performance is still limited and inconclusive in specific sports, such as archery. 7 Besides intravenous and oral administration of beta-blockers, ophthalmic drops containing beta-blockers are also prohibited. Indeed, beta-blocker ophthalmic drops induce the systemic adrenergic effect on cardiopulmonary functions through the nasolacrimal duct and the conjunctival vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis is used by athletes to reduce the anxiety level to attain better sleep quality and better muscular tonicity [8]. Also the beta-blockers are widely used by athletes to reduce the heart rate and anxiety among them [9]. Social phobia is recognized as fear of negative evaluation and loneliness in social situations that is especially seen in athletes and musicians [10].…”
Section: Introductionmentioning
confidence: 99%